Santos e Madonas de Alfredo Volpi : reinvenção da tradição ou liberdade experimental? - Magalhães, Jorge da Silva (2015)
This thesis proposes to analyze the artistic production of themed religious of Alfredo Volpi, considering relevant peripheral contexts, such as the sociopolitical situation of the time and the direct contact that the artist had with the frescoes of pre-Re